2016
DOI: 10.1007/s00253-016-7992-8
|View full text |Cite
|
Sign up to set email alerts
|

PpEst is a novel PBAT degrading polyesterase identified by proteomic screening of Pseudomonas pseudoalcaligenes

Abstract: A novel esterase, PpEst, that hydrolyses the co-aromatic-aliphatic polyester poly(1,4-butylene adipate-co-terephthalate) (PBAT) was identified by proteomic screening of the Pseudomonas pseudoalcaligenes secretome. PpEst was induced by the presence of PBAT in the growth media and had predicted arylesterase (EC 3.1.1.2) activity. PpEst showed polyesterase activity on both whole and milled PBAT film releasing terephthalic acid and 4-(4-hydroxybutoxycarbonyl)benzoic acid while end product inhibition by 4-(4-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 40 publications
1
70
0
1
Order By: Relevance
“…The monomer Ta represented the most abundant compound detected at all experimental conditions and was proven not to be metabolised by the organism. This suggests the involvement of the fungus extracellular enzymes in the cleavage of aromatic ester bonds present in PBAT chains 17,45 , which are reportedly less prone to hydrolysis than the ester bond with aliphatic monomer (adipic acid) as also described for P. pseudoalcaligenes polyesterase PpEst 15 . Previous studies on single enzyme hydrolysis process of milled PBAT reported that BTaB and BTa were more abundant than the monomer, as well as that an increase of Ta concentration is given by higher pH than that selected in the current study 7 .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The monomer Ta represented the most abundant compound detected at all experimental conditions and was proven not to be metabolised by the organism. This suggests the involvement of the fungus extracellular enzymes in the cleavage of aromatic ester bonds present in PBAT chains 17,45 , which are reportedly less prone to hydrolysis than the ester bond with aliphatic monomer (adipic acid) as also described for P. pseudoalcaligenes polyesterase PpEst 15 . Previous studies on single enzyme hydrolysis process of milled PBAT reported that BTaB and BTa were more abundant than the monomer, as well as that an increase of Ta concentration is given by higher pH than that selected in the current study 7 .…”
Section: Discussionmentioning
confidence: 57%
“…Microbial activities against PBAT have been shown in bacteria and to a lesser extent in fungi from soil [13][14][15][16][17] , by esterolytic hydrolases 7,15,18,19 . Typically, the investigation of PBAT degrading enzymes involves functional screenings and protein isolation through chromatographic purification 14,16,20,21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Members of these orders were also found among the isolated strains obtained from the incubated plastics. Especially Pseudomonas is well known for its broad metabolic capabilities, and various strains of the genus are associated with the degradation of PLA, PBAT, PE, and many other plastics (Wallace et al, 2017;Wilkes and Aristilde, 2017;Bubpachat et al, 2018). Burkholderiales possess a broad range of enzymes able to degrade polyaromatic hydrocarbons (PAHs), which include important soil pollutants (Pérez-Pantoja et al, 2012).…”
Section: Bacterial Key Taxa Associated With Plasticsmentioning
confidence: 99%
“…By using a hidden Markov Model‐based search strategy to screen sequence data sets, Danso and co‐authors showed that a surprisingly large variety of potential polyesterases is still to be discovered, in particular in bacteria which are currently not considered as a prime source for cutinases (Danso et al ., ). Pseudomonas species may constitute an example; in the context of polymer hydrolysis, they appeared as a source for enzymes hydrolyzing polyurethane (Wilkes and Aristilde, ) for a long time, but some very recent reports by the Guebitz group indicated also polyesterase activity in Pseudomonads (Haernvall et al ., ,; Wallace et al ., ). The here reported confirmation of polyesterase activity of bacteria from the P. pertucinogena lineage, that was already suggested by sequence homology searches (Bollinger et al ., ), underlines the biotechnological potential of this group of bacteria.…”
Section: Discussionmentioning
confidence: 97%